2013
DOI: 10.1002/hyp.10072
|View full text |Cite
|
Sign up to set email alerts
|

Fire severity and surface rock fragments cause patchy distribution of soil water repellency and infiltration rates after burning

Abstract: Although fire-induced soil water repellency (SWR) and its effects on soil hydrology and geomorphology have been studied in detail, very few studies have considered the effect of rock fragments resting on the soil surface or partly embedded in soil. In this research, we have studied the effect of rock fragments on the strength and spatial distribution of fire-induced SWR at different fire severities. A fireaffected area was selected for this experiment and classified into different zones according to fire sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 101 publications
3
18
0
Order By: Relevance
“…The effects of different rock fragment cover treatments on soil loss are shown in Table . Soil loss decreased with increasing rock fragment coverages in cases where rock fragments were resting on the soil surface, which was comparable to previous results (Fang, Shi, Chen, Zhang, & Wang, ; Gordillo‐Rivero, García‐Moreno, Jordán, Zavala, & Granja‐Martins, ). The mean soil loss rate was small (5.5 g m −2 min −1 ) for RL when R c = 40%, which was much less than that in bare land (10.8 g m −2 min −1 ).…”
Section: Resultssupporting
confidence: 90%
“…The effects of different rock fragment cover treatments on soil loss are shown in Table . Soil loss decreased with increasing rock fragment coverages in cases where rock fragments were resting on the soil surface, which was comparable to previous results (Fang, Shi, Chen, Zhang, & Wang, ; Gordillo‐Rivero, García‐Moreno, Jordán, Zavala, & Granja‐Martins, ). The mean soil loss rate was small (5.5 g m −2 min −1 ) for RL when R c = 40%, which was much less than that in bare land (10.8 g m −2 min −1 ).…”
Section: Resultssupporting
confidence: 90%
“…At 800 o C, water repellency begins to diminish after only 10 minutes and is completely destroyed after 20 minutes, while soil renders completely wettable after only 10 minutes at 900 o C (DeBano and Krammes, 1966). Field studies have shown that rock fragments on the soil surface cause an heterogeneous pattern of temperature gradients, which contribute to enhance and/or destroy water repellency (Gordillo-Rivero et al, 2013).…”
Section: Soil Water Repellencymentioning
confidence: 99%
“…However, the relationship between SWR response and temperature is not as easy as it appears. SWR development, induction, enhancement or decrease, depends on many other factors such as the nature of atmospheric heating (Bryant et al, 2005), the quantity and quality of soil organic matter content, soil moisture (Doerr et al, 2000), soil texture (Arcenegui et al, 2007), mineralogy of clay fraction (Mataix-Solera et al, 2008) or even rock fragments (Gordillo-Rivero et al, 2014). In our case, SWR increased at low temperatures when natural SWR was initially present and was mainly caused by the high SOC content (Gata and Aitana samples, clay and clay loam soils, respectively).…”
Section: Soil Water Repellency and Soil Organic Carbon Response To Hementioning
confidence: 99%